Shape and Unification Pattern of Palatal Rugae as a Race Identification Tool- A Cross-Sectional Study - Firoz Ismail; Rejeesh.E.P; Rajesh.H; Nabeel Abdul Vahid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: One of the integral parts of forensic medicine is identification of individuals from biologicalsamples and from the anatomical signatures. Identification of individuals, races, species, gender from theanatomical signatures of teeth and oral cavity is one of such branches which existed in practice in crudeform even before origin of the Forensic odontology as a specialization. Individual variations in Palatal rugaepattern, and its biometric value as a potential tool for establishment of identity was reported centuries back. It’snot standardised or included in the regular standard protocols even today in the age of artificial intelligence.In this pilot study we are comparing two racial groups i.e., Indian and Malaysian with established parametersfor palate rugae with an objective of testing feasibility and validation for identification of individuals andracial groups and also to provide preliminary data for larger studies.Aims and Objectives: The aim of this pilot study is to explore the feasibility of palate rougoscopy as a toolfor race identification by studying the shape and unification Pattern of Palatal Rugae in Indian and Malaysianpopulation.Methodology: Study population was male Indian and Malaysian Medical and Dental students, aged 18-25years studying at Mangalore, India. Sample size 80 (40 in each group); were selected for studying PalatalRugae. The palate impressions were collected using maxillary alginate cast. The parameters assessed were:shape an unification based on classification of Thomas & Kotze. Comparison for two populations was doneusing non-parametric Mann-Whitney Test.Results : Predominant Shape: The Curvy patterns were more common in Malaysians compared to Indian.The Wavy patterns were more common in Malaysians than Indians.The Circular patterns were more commonin Indians than Malaysians.Predominant unification: Diverging patterns were more in Malaysians than Indians and Converging patternswere more in Indians than Malaysians and statistically significant.Conclusion : In the present study the Malaysians had predominantly curvy and wavy patterns and Indianshad circular shapes. Straight patterns were seen equally in both the populations. Although unification ofthe palate rugae was seen, the diverging patterns is more in Malaysians and Converging patterns more inIndians.